พฤติกรรมการดื่มสุรา และปัจจัยที่เกี่ยวข้องของพนักงานต้อนรับบนเครื่องบิน - ปวีณา จินต์สวัสดิ์ (จุฬาลงกรณ์มหาวิทยาลัย, 2004)
This study was a cross-sectional descriptive study. The objectives of this study were to estimate the prevalence of alcohol use. to determine the related factors of alcohol drinking, and to explore the characteristics of cabin crews drinking behavior. The samples consisted of 402 cabin crews. The instrument was a set of questionnaires consisting of 3 parts: demographic questionnaire, Brief Michigan Alcoholism Test (BMAST), and Alcohol Use Inventory (AUI). Data was analyzed by SPSS for Windows. Statistics utilized were mean, percentage, standard deviation, maximum, minimum. Chi-square test, Fisher s Exact test. One-way Analysis of Variance, Multiple comparison: Scheffe s method, and Multiple Linear Regression analysis. The result of the study indicated that the point prevalence of alcohol drinking behavior of cabin crews was 59.1%. Fifty two point six percent of samples were normal drinkers, 1.2% were suggestive alcoholism drinkers and 5.2% were alcoholism drinkers. The chi-square test revealed that sex, smoking, history of use or nonuse illicit drugs, family s members alcohol drinking history, family relationship and having peers drinking alcohol were associated with cabin crews alcohol drinking behavior. By using multiple linear regression analysis, The 9 factors at p<.05 which could be predictive variables of alcoholism were having peers drinking alcohol, family relationship, and having conflicts with supervisors (R²=27.2). Most of subjects in this study obtained the scores of normal ranges in all 6 aspects of characteristics of drinking. The result showed that 32.5% of cabin crews got the high scores on drinking to enhance functioning, 3.4% on obsessive, compulsive, and sustained drinking, 0.8% on uncontrolled life disruption (directly expressed), 0.8% on uncontrolled life disruption (indirect stated), and 1.7% on anxious concern about drinking and acknowledgement and 0% on awareness of drinking problems.